Knowledge, awareness and compliance among dental professionals regarding percutaneous exposure incidents as occupational hazard - Permi, Shwethashri R.; Bhandary, Rahul; Thomas, Biju (Journal of Health and Allied Sciences NU, 2015)
Percutaneous injuries constitute one of the most common occupational health hazards in healthcare profession. Dental professionals are at more risk of acquiring these injuries due to their limited and restricted working area in mouth. This was a cross-sectional study done among dental professionals in Mangalore, Dakshina Kannada, Karnataka state India to access Knowledge awareness and compliance among dental professionals regarding percutaneous exposure incidents. This study concludes that Dental professionals are at a high risk of occupational disease due to accidental exposure to infected blood and body fluids. for which appropriate measures not taken after one such exposure There is a need of clearing the present misconceptions through educational training programs early in the study period and providing facilities for reporting, documenting, supportive and proper guidelines regarding percutaneous injuries in work place for healthy community.
Keywords: Percutaneous exposure; Body fluids contamination; post exposure prophylaxis